The Increased Ability of the Third-Grade Students in Story Writing through Personal Journal Writing Instruction at the Elementary School - Ratna Trieka Agustina (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
This study was aimed at describing the increased ability of the third grade students in story writing through the personal journal writing instruction at the elementary school of Bendogerit IV, Blitar Municipality. Nine students were chosen as the subjects of this study and they were divided into three categories of low, middle, and high achievers. The results of this study showed that the low-category students increased their writing competence of 50%, 40%, and 50% respectively. In the same way, the middle-category students progressed at different levels of 68%, 68%, and 45% respectively. Similarly, students of the fast category improved the writing ability of 45%, 72%, and 65% respectively.